Transformative Epistemology in Islamic Education: Linking Spirituality and Rationality in the Modern Education Curriculum - Neng Wina Shalehah (CV. Intake Pustaka, 2026)
This article aims to explore the concept of transformative epistemology in the context of Islamic education, which links spirituality and rationality in the development of modern educational curricula. Through a qualitative approach and literature study, this article discusses how Islamic education can integrate aspects of spirituality and rationality to create a curriculum that is not only based on the teaching of science, but also on the formation of the character and spirituality of students. This research identifies challenges and opportunities in the application of transformative epistemology in Islamic schools and how an inclusive curriculum can create a balance between spiritual and intellectual dimensions. The implications of this study show that the application of transformative epistemology in Islamic education can enrich the existing curriculum and provide a strong foundation for students' personal development.